PENINGKATAN HASIL BELAJAR IPS DENGAN MENGGUNAKAN MODEL PROBLEM BASED LEARNING DI SD - Agus Sari, Imelda Eka (e-Jurnal Inovasi Pembelajaran Sekolah Dasar, 2013)
This research is Classroom Action Research used qualitative and quantitative approaches. The purpose of this study is to describe the planning, implementation, observation and reflection. Subjects in this research are the teacher and students. The result of the research shows: a) Planning in cycle I meeting I with percentage 67,86 %, meeting II with percentage 82, 14 % and cycle II with percentage 96,43 %. b) Implementation in cycle I meeting I from teacher is 69,11 %, meeting II is 79,41 % and cycle II is 82,35 %. Implementation from students in cycle I meeting I is 61,76 %, meeting II is 75 % and cycle II is 89,71 %. c) The result of learning assessment in cycle I meeting I is 68,26%, meeting II is 70,71 % and cycle II is 85,32 %. In conclusion, Problem Based Learning (PBL) method can increase students’ outcomes; both score and interest in learning IPS at SD Negeri 11 Bukit Apit Puhun Kota Bukittinggi grade IV.   Kata Kunci: hasil belajar, pembelajaran IPS, problem based learning (PBL)